O adultério como tática de subversão do matrimônio por parte das matronas no Alto Império romano a partir da parenética satírica dos Epigramas, de Marcial, Sátiras, de juvenal e Satiricon, de Petrônio (Séculos I A.E.C. – II D.E.C.). - ARAUJO, Alexandro Almeida Lima (2019)
The present work has as focus of analysis the Roman matrons and the committal of adulteries in the period of the Principality of Rome. Through the condemnation of illegitimate sexual intercourse practiced by materfamilias through epigrammatic rhetoric, we can visualize the way in which the society in question saw the sacred marriage and the ties with the ancestral past. This ancestral past, supported in the mos maiorum (values of the ancients), would be represented in the gens and, therefore, there would be attempts of control so that the order of shoots was not adulterated and disturbed the deities. These strategic attempts at control can be seen in Petronius' Latin writings with Satiricon; Martial, with Epigrams; and Juvenal, with Satire. Ovid, with Amores, becomes a case apart, because his poetry does not possess moral judgments aimed at properly condemning adulteries. However, with this document it is possible to understand issues that pervade vigilance over the mother and the idea of reserving the girl's body for legitimate procreation. The laws of Augustus on marriage and adultery become pertinent to the discussion because of the establishment of rules and norms. Norms that defined, in theory, a restraint to the fraudulent carnal relations, but that in the present practice, as Michel de Certeau points out, the norm suffered clashes and confrontations. This parthenic poetry of the rethor will be understood as ideological, and thus M. Bakhtin and P. Ricoeur are brought into a dialogue in which ideology revolves around power, and words, purposely chosen, would fulfill a moral and sacred ideological function. Together with these authors the thinking of M. Foucault is made present on the relations of power and the discourse as strategic, besides thinking the memories, in the conception of Jacques Le Goff, like manufactured in the bulge of the relations of force.